2020
DOI: 10.3390/foods9091229
|View full text |Cite
|
Sign up to set email alerts
|

Do Your Kids Get What You Paid for? Evaluation of Commercially Available Probiotic Products Intended for Children in the Republic of the Philippines and the Republic of Korea

Abstract: A wide range of probiotic products is available on the market and can be easily purchased over the counter and unlike pharmaceutical drugs, their commercial distribution is not strictly regulated. In this study, ten probiotic preparations commercially available for children’s consumption in the Republic of the Philippines (PH) and the Republic of Korea (SK) have been investigated. The analyses included determination of viable counts and taxonomic identification of the bacterial species present in each formulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 90 publications
(93 reference statements)
0
10
0
1
Order By: Relevance
“…In addition, advanced formulations or strain characteristics often require optimised protocols, and protocols developed by manufacturers are often not available. Nevertheless, several recent studies conducted in different parts of the world, such as China, United States–Canada, Philippines–Korea, Italy–France, and Poland, have demonstrated through plate counting that products that do not comply with labels are still regularly found in the market ( Chen et al, 2017 ; Di Pierro et al, 2019 ; Korona-Glowniak et al, 2019 ; Dioso et al, 2020 ; Shehata and Newmaster, 2020 ). Chen et al (2017) reported that viable cells could not be recovered from two (25%) probiotic supplements from the Chinese market.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In addition, advanced formulations or strain characteristics often require optimised protocols, and protocols developed by manufacturers are often not available. Nevertheless, several recent studies conducted in different parts of the world, such as China, United States–Canada, Philippines–Korea, Italy–France, and Poland, have demonstrated through plate counting that products that do not comply with labels are still regularly found in the market ( Chen et al, 2017 ; Di Pierro et al, 2019 ; Korona-Glowniak et al, 2019 ; Dioso et al, 2020 ; Shehata and Newmaster, 2020 ). Chen et al (2017) reported that viable cells could not be recovered from two (25%) probiotic supplements from the Chinese market.…”
Section: Discussionmentioning
confidence: 99%
“…Five out of 10 (50%) tested products available in Poland did not reach the number of viable bacteria claimed by the manufacturer ( Korona-Glowniak et al, 2019 ). One in 10 (10%) probiotic preparations available for consumption by children in the Republic of the Philippines and the Republic of Korea contained a lower number of viable microorganisms than claimed on the label ( Dioso et al, 2020 ). The number of viable microorganisms determined in 72 samples of probiotic products from the United States and Canada was lower than labelled in 5 samples (6.9%), including one product that had no viable cells ( Shehata and Newmaster, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations